(untitled) (Journal of Hama University, 2024)
The research was conducted in one of the private lambs fattening farms in the Damascus countryside governorate on 15 lambs whose weight ranged between (24-25) kg. (Group I: The control group. Group II: replaced the dry barley with barley culture with 20% of the concentrated ration. Group III: The dry barley was replaced with the barley culture with 40% of the concentrated ration.) The experiment lasted for 60 days, preceded by a 10-day preparatory feeding period, and the feed mixtures were close in nutritional value in terms of energy and protein according to the nutritional needs of the age group according to the American Food Standard (NRC, 1985) and differed among themselves by the percentage of cultivar barley, and the indicators were studied The following productivity (live weight - weight gain - the amount of feed consumed - food conversion factor - economic feasibility). The results showed a significant increase at the level (P<0.05) in the mean live weight in the average daily and total weight gain and the feed conversion factor when replacing dry barley grain with cultivar by 40%, and the replacement group achieved 40% the lowest cost per kilogram for weight gain and the highest profit index. Compared to other experiment groups. the concluded from the study that replacing dry barley grains with cultivar barley for fattening rations improves the production efficiency, and the replacement ratio is 40% is the best among the study ratios.0